Interrelationships between policies to encourage biofuels, energy efficiency and climate change mitigation: A synergistic analysis focusing on the Brazilian RenovaBio Program - Kutianski José Romeiro, Laércio; Simões, André Felipe; Massao Kurita, Rodrigo (Latin American Journal of Energy Research, 2021)
Brazil, which has a typically renewable energy matrix and as one of the world leaders in biofuel production, approved, in 2017, the implementation of a policy to promote biofuels related to the reduction of Greenhouse Gas (GHG) emissions through the Program RenovaBio. Brazil is part of a small group of countries with a typically renewable energy matrix, unlike the average world matrix, which is basically of fossil origin. It is urgent to emphasize that despite the growing importance that several countries have shown by inserting goals to reduce GHG emissions in their economic programs, fossil fuels still represent a demand driver for most economic hubs. Thus, the objective of this work, exploratory and focusing on policies aimed at promoting the supply and consumption of biofuels in Brazil and blocks of countries, is to synergistically analyze any technological, regulatory, and economic discrepancies between developed and developing countries. At the same time, the objective is to contribute to a broader understanding of the role of energy efficiency and biofuels for the establishment of a low-carbon economy at a global level. To this end, as methodological paths, an in-depth systemic bibliographic review was undertaken, centrally based on refereed scientific journals and reports from public and private agencies produced in Brazil and abroad working in the area of ​​biofuels, energy efficiency, and mitigation of climate changes. It was found that the design and realization of a low carbon economy that compares the substantial reduction in global GHG emissions throughout the current 21st century and means that the average temperature of the earth's surface does not exceed 2 ºC by 2100, as preconized by the current Paris Agreement, inevitably, requires energy efficiency measures based on policies to promote the production and consumption of biofuels.Keywords: Climate Change mitigation. Biofuels. Energy Efficiency. Brazilian’s Renovabio Program. Paris Agreement.